Promoting Green Consumption Intentions in Vietnam: The Role of Consumption Values in Shaping Attitudes Towards Green Consumption Behavior - Hoang Thu , Thao; Nguyen Ngoc Huynh, Nhu; Le Pham Khanh , Van; Pham Nguyen Thu , Hang; Tran Ngoc Phuong , Linh; Nguyen Ngoc Phuong , Minh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2024)
This study aims to investigate the factors that promote Vietnamese consumers’ purchase intentions for green products through lenses of the Theory of Consumption Value (TCV) and the Theory of Planned Behavior (TPB). The survey of 248 consumers in Ho Chi Minh City, Vietnam was conducted. The results revealed that functional value – price, social value, and emotional value, environmental value have a significant positive relationship with consumer attitude towards green products. Attitude also acts as a mediator in the relationship between these factors and consumers’ intention to purchase green products. The authors find no evidence on the relationship between functional value – quality, conditional value, epistemic value with consumer attitudes. This inquiry extends the literature on consumer behavior in a sustainable consumption context by identifying the mediation mechanisms underlying this link. This paper concludes with implications of the findings for marketers, as well as potential directions for further research.